Skreening Fungsi Hati pada Wanita Pekerja Seksual (WPS) di Pasar Porong Sidoarjo - Arif Rahman Nurdianto; Farida Anwari; Amellya Octifani; Fery Setiawan; Rizal Fauzi Nurdianto; Elis Anita Farida; Dyah Ayu Febiyanti; Martina Kurnia Rohmah (Jurnal SADEWA, 2024)
Female Sexual Workers (FSW) are a group that is very at risk of transmitting HIV/AIDS and so are their customers. They usually engage in unsafe sexual behavior. From the health aspect point of view, they are often seen as a medium for the spread of dangerous infectious diseases, such as: HIV/AIDS, hepatitis, sexually transmitted diseases, especially unsafe commercial sex practices. FSW rarely pay attention to their customers' status, such as their HIV infection status, so the FSW population is at risk if they engage in unsafe sexual relations, such as not using safety devices (condoms). Sidoarjo Regency is the district that has the highest number of HIV sufferers in East Java, due to the very high mobility of the population which is supported by wild locations and night entertainment venues which are widely spread across sub-district points/spots, thus allowing very high transmission of HIV disease, considering HIV is transmitted through sexual contact. The planned screening activities will be carried out on 18 WPS in the Sidoarjo Regency area, especially in the Porong area. Screening was carried out by checking the complete blood count of 18 FSW subjects to take precautions regarding the dangers of alcohol consumption and the use of whitening creams for beauty purposes to attract customers. Consuming alcohol and using bleaching cream can cause kidney and liver problems, so it is necessary to carry out liver function tests regularly and periodically